Virtual Supervision of Third Year Medical Students Using Handheld POCUS Devices and Cloud-based Image Archiving Provides Opportunity for Feedback and Skill Improvement - Sydney Murray; Krista Trinder; Linden Kolbenson; Jeremy Katulka; Paul Olszynski (CINQUILL Medical Publishers Inc., 2023)
Background: Feedback on Point of Care Ultrasound (POCUS) skills is essential for skill development. Providing feedback can be difficult in a large province with several distributed medical education sites. Use of handheld POCUS devices and a cloud-based image archiving enables virtual supervision. We evaluated the quality of uploaded images as well as feedback provided to students.  Methods: Volunteer third year students were given access to handheld POCUS devices at various training sites. Students were encouraged to upload educational POCUS scans to their accounts where they would then receive feedback from faculty. Subsequently, images that met inclusion criteria were randomized and reviewed by a blinded expert using a global rating scale. Feedback was also analyzed. Finally, students completed a questionnaire on their technology-enhanced POCUS learning experience.  Results: An independent-sampled t-test comparing mean ratings for initial images submitted prior to any feedback with those submitted after three rounds of feedback showed significant effect on image scores (2.60 vs 3.50, p = .040, d = .93). Feedback included 4 performance domains (indications, image generation, interpretation, and integration). Students found the technology easy to use and felt feedback was tailored to their learning needs.  Conclusions: We observed that virtual feedback provided to medical students through a cloud-based work platform can be effective for enhancing POCUS skills.